Moscow rules - Silva, Daniel (Penguin, 2008)
The death of a journalist leads Gabriel Allon to Russia, where he finds that, in terms of spycraft, even he has something to learn. He's playing by Moscow rules now. Ivan Kharkov, a former KGB colonel who built a global investment empire on the rubble of the Soviet Union, is an arms dealer and he is about to deliver Russia's most sophisticated weapons to al- Qaeda. Unless Allon can learn the time and place of the delivery, the world will see the deadliest terror attacks since 9/11 and the clock is ticking fast.